2011
DOI: 10.1384/jsa.17.247
|View full text |Cite
|
Sign up to set email alerts
|

Properties of TaN Films for ULSIs Prepared by Reactive Sputter Deposition

Abstract: Tantalum Nitride (TaN) thin films were deposited onto n-type Si(100) and (111) substrates with SiO 2 films at room temperature by radio frequency (RF) magnetron sputtering under Ar-N 2 plasma using a tantalum target. We observed the formation of TaN thin films with a wide range of the electrical resistivity as a function of the N 2 gas flow ratio, working pressure and the sputtering power, and their origins are discussed based upon the structural properties and chemical compositions of TaN thin films before Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…2. There is a tendency that the electrical resistivity increases with increasing TaN (111) peak intensity, which is the same with our previous observation that the electrical resistivity of TaN(200) preferentially oriented films was lower than that of TaN(111) preferentially oriented films [7]. At 600…”
Section: Methodssupporting
confidence: 90%
See 3 more Smart Citations
“…2. There is a tendency that the electrical resistivity increases with increasing TaN (111) peak intensity, which is the same with our previous observation that the electrical resistivity of TaN(200) preferentially oriented films was lower than that of TaN(111) preferentially oriented films [7]. At 600…”
Section: Methodssupporting
confidence: 90%
“…• C), low electrical resistivity and high thermal conductivity [1][2][3][4][5][6][7], which make it possible to use as a diffusion barrier between Copper (Cu) wiring and interlayer dielectric film in ultra large scale integrated circuits (ULSIs) [2][3][4][5][6][7][8][9][10]. TaN can also be used in wide variety of applications such as corrosion-resistant materials, write-head materials in high-density magnetic recording and high-speed thermal printing head as well as thin film resistors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high hardness of ≈ 61.9 GPa corresponds to orthorhombic Ta 4 N phase. Tajima et al [11] have also shown that the resistivity, film thickness, and crystallographic structure of TaN thin films could be controlled by changing N 2 gas flow ratio, working pressure and sputtering power for the application to ultra large-scale integration (ULSI). Kwang et al [12] studied optical properties and X-ray photoelectron spectroscopy of TaN thin films prepared by means of a reactive RF sputtering method on borosilicate glass substrates.…”
Section: Introductionmentioning
confidence: 99%